AN ANALYSIS OF LANGUAGE CHOICE OF INTERETHNIC MARRIAGE DYAK-MADURESE COUPLES - Sari, Riski Amrina (HUMANIKA, 2020)
This research explained the choice of language for Dyak-Madurese couples with interethnic marriage. In this research there are the aims of the research, this research aims to investigate the language choice used by interethnic marriage Dyak-Madurese families and to investigate the factors affecting language choice of interethnic marriage Dyak-Madurese couples. The method of this research was descriptive qualitative research. The researcher selected three families of Dyak-Madurese interethnic marriage as participants to achieve the aim of the research. The data were obtained by observing and interviewing. The results of this research have shown that interethnic marriage families Dyak-Madurese prefer the Indonesia language as their first language and are commonly used in everyday contact at the home domain. This research found that the children of the third family preferred a different language when interacting with their father, he preferred the Madura language, but he also uses the Indonesia language when communicating with his parents. The finding also showed that interethnic marriage Dyak-Madurese families use the Indonesia language in another domain such as neighborhood domain and with friends. The research also found that the children of the first and second families from interethnic marriage families were unable to speak the ethnic language, it has caused the younger children not to be taught the ethnic language. The children of the third family can speak Madura language because the father taught him the Madura language. In data there are three factors affecting language choice in interethnic marriage Dyak-Madurese couples, they are the participant, social context, the function of the language. Based on the research the interethnic marriage Dyak-Madurese families show a negative attitude toward their ethnic language, but the father of the third family has a positive attitude.